The Role of Brand Image in Mediating the Influence of Social Media Marketing on Purchase Intention (Study on JEN Coffee in Denpasar City) - Albany, Anak Agung Ngurah Agung Danan; Respati, Ni Nyoman Rsi; Piartrini, Putu Saroyini (Asian Journal of Management Analytics, 2025)
Purchase intention refers to the strong desire of customers to acquire a particular commodity or service because they have high expectations about its value or benefits.   The aim of this research is to determine how purchase intention is influenced by brand image through social media marketing.   The study was conducted at JEN Coffee in Denpasar City.   In this study, 120 participants were selected by a purposive sample strategy.   A survey approach was used to collect data, with a questionnaire acting as the study tool. Descriptive and inferential statistics, as well as path analysis, were employed data processing techniques. The study found that purchase intention was significantly and favorably impacted by social media marketing, that brand image was significantly and favorably impacted by social media marketing, and that brand image was able to mediate the relationship between these two factors. The study's findings suggest that businesses might use social media marketing more frequently to enhance brand perception and raise the possibility that customers would make a purchase.